ANALISIS PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA PT. FITRA WIKA - Simmon, Alex; Septiana, Tian; Ramadhania Putri, Nadila (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2021)
The rapid development of the world requires business people to develop the implementation of a better corporate governance system. This research is a qualitative research with data collection methods using interview and observation techniques. The purpose of this research is to find out how the application of the principles of good corporate governance in PT. Fitra Wika. The results showed that on the principle of transparency, the company has provided information to internal and external parties. The submission is made orally and in writing. On the principle of accountability, the company has an internal control system, performance measures, and company targets. on the principle of responsibility, the company has carried out its corporate social responsibility by not polluting the environment, providing social assistance, and complying with government regulations. On the principle of independence, the company does not have any intervention from other parties. In fairness, every part of the company gets the same treatment.